2020
DOI: 10.1002/jsfa.10407
|View full text |Cite
|
Sign up to set email alerts
|

Screening antagonistic yeasts against citrus green mold and the possible biocontrol mechanisms of Pichia galeiformis (BAF03)

Abstract: BACKGROUNDPenicillium digitatum is one of the most important pathogens causing citrus green mold, leading to significant economic losses. Traditionally, synthetic fungicides are used to control diseases. However, the side effects of fungicides should not be ignored. Thus, antagonistic yeasts were proposed to be safe and effective alternatives for managing diseases. Orchards are excellent sources of naturally occurring antagonists against pathogens. Therefore, in the present study, antagonistic yeasts obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Previously, it has been repeatedly shown that P. kudriavzevii (and other representatives of this genus) has a strong antagonistic effect on both mold and phytopathogenic fungi 33‐35 . It has been suggested that this species could be utilized for practical purposes in the protection of agricultural products from mold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been repeatedly shown that P. kudriavzevii (and other representatives of this genus) has a strong antagonistic effect on both mold and phytopathogenic fungi 33‐35 . It has been suggested that this species could be utilized for practical purposes in the protection of agricultural products from mold.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been repeatedly shown that P. kudriavzevii (and other representatives of this genus) has a strong antagonistic effect on both mold and phytopathogenic fungi. [33][34][35] It has been suggested that this species could be utilized for practical purposes in the protection of agricultural products from mold. The compost itself (even BSFL-free, after removal the larvae) could possibly have an anti-fungal effect, providing a positive effect on plant growth and health.…”
Section: Discussionmentioning
confidence: 99%
“…Pichia galeiformis has been reported with efficient control of postharvest green mold in citrus through competition for space and nutrients as well as production of volatile organic compounds . However, the effect of P.…”
Section: Introductionmentioning
confidence: 99%
“…The VOC 2-phenylethanol is reported as a common inhibitory compound produced by several biocontrol yeasts including Debaryomyces nepalensis , Wickerhamomyces anomalus , Metschnikowia pulcherrima , Saccharomyces cerevisiae , and Pichia manshurica (formerly, Pichia galeiformis ) ( Zhou et al, 2018 ; Contarino et al, 2019 ; Chen et al, 2020 ). In this study, we found a strong inhibitory effect of 2-phenylethanol on germination and mycelium growth of C. inversicolor and P. roqueforti at 10 –3 mol/L.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that efficient mold inhibition relied on additive or synergistic effects of the yeast inhibition factors such as competition for nutrients and space as well as production of soluble compounds or VOCs ( Núñez et al, 2015 ). Similarly, P. manshurica has been shown to colonize and amplify quickly in citrus wounds and further to produce eight VOCs, including acetic acid and 2-phenylethanol during growth, which inhibited growth of Penicillium digitatum , causing citrus green mold ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%